Preparation, Characterization and Antimicrobial Properties of Nanosized Silver‐Containing Carbon/Silica Composites from Rice Husk Waste. Issue 12 (13th December 2021) - Unglaube, Felix; Lammers, Alexander; Kreyenschulte, Carsten Robert; Lalk, Michael; Mejía, Esteban
Abstract: Rice husk, one of the main side products in the rice production, and its sustainable management represent a challenge in many countries. Herein, we describe the use of this abundant agricultural bio‐waste as feedstock for the preparation of silver‐containing carbon/silica nano composites with antimicrobial properties. The synthesis was performed using a fast and cheap methodology consisting of wet impregnation followed by pyrolysis, yielding C/SiO2 composite materials doped with varying amounts of silver from 28 to 0.001 wt %. The materials were fully characterized and their antimicrobial activity against ESKAPE pathogens, namely E. faecium, S. aureus, K. pneumoniae, A. baumannii, P. aeruginosa, and E. coli, and the pathogenic yeast C. albicans was investigated. Sensitivities of these strains against the prepared materials were demonstrated, even with exceptional low amounts of 0.015 m% silver. Hence, we report a straightforward method for the synthesis of antimicrobial agents from abundant sources which addresses urgent questions like bio‐waste valorization and affordable alternatives to increasingly fewer effective antibiotics. Abstract : Silver nanoparticles supported on carbon/silica composites have been prepared by a simple method from rice husk. These novel materials display very high antimicrobial activity against ESKAPE pathogens ( E. faecium, S. aureus, K. pneumoniuae, A. baumannii, P. aeruginosa, and E. coli ) as well as C. albicans . It represents a cheap alternative for the valorization of the overabundant rice bio‐waste with potential direct use in filters for water sanitation or in medical applications.